2019
DOI: 10.1016/j.cmet.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

A Map of Human Type 1 Diabetes Progression by Imaging Mass Cytometry

Abstract: Highlights d Highly multiplexed imaging of pancreas tissues from human donors with T1D d Islet evolution through T1D progression inferred from snapshot data d The phenotype of b cells is altered prior to b cell destruction d T cell recruitment depends on both disease stage and islet profile

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
286
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(305 citation statements)
references
References 48 publications
19
286
0
Order By: Relevance
“…Recent studies applied advanced imaging mass cytometry techniques to compare the human pancreas in T1D patients and in control individuals. Changes were found in islet structure and size, vascularization, and levels of various immune cells, as well as progressive cell loss preceded by infiltration of cytotoxic and helper T cells in the pancreatic islets (Damond et al, 2019; Wang et al, 2019). However, the analysis of stages during T1D progression is complicated for multiple reasons, particularly the late manifestation of the disease and limited availability of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies applied advanced imaging mass cytometry techniques to compare the human pancreas in T1D patients and in control individuals. Changes were found in islet structure and size, vascularization, and levels of various immune cells, as well as progressive cell loss preceded by infiltration of cytotoxic and helper T cells in the pancreatic islets (Damond et al, 2019; Wang et al, 2019). However, the analysis of stages during T1D progression is complicated for multiple reasons, particularly the late manifestation of the disease and limited availability of samples.…”
Section: Introductionmentioning
confidence: 99%
“…Single cell assays such as mass cytometry (CyTOF), along with other new methods designed to profile the proteome at high resolution and with minimal cell input [108,109], can offer insights into cellular heterogeneity but cannot discern cell-cell interactions or orientation within the native tissue environment (Table 3). In contrast, Imaging Mass Cytometry (IMC), which facilitates visualization of tissue sections labeled with antibodies conjugated to rare metal isotopes using high-resolution laser ablation and time-of-flight mass spectrometry, allows for high-parameter in situ data acquisition without the compensation issues plaguing traditional immunofluorescence analyses [110,111] (Table 3). Simultaneous detection of 36 parameters from a single tissue section by IMC coupled with analysis of pseudotime dynamics indicated that β-cells lose identifying markers such as insulin, proinsulin, IAPP, and protein tyrosine phosphatase receptor type N (PTPRN) prior to their destruction [111], potentially indicating a direct role for β-cells in inciting their own destruction by autoreactive T cells.…”
Section: Multiplexed Analyses Of Human Pancreas Tissuementioning
confidence: 99%
“…In contrast, Imaging Mass Cytometry (IMC), which facilitates visualization of tissue sections labeled with antibodies conjugated to rare metal isotopes using high-resolution laser ablation and time-of-flight mass spectrometry, allows for high-parameter in situ data acquisition without the compensation issues plaguing traditional immunofluorescence analyses [110,111] (Table 3). Simultaneous detection of 36 parameters from a single tissue section by IMC coupled with analysis of pseudotime dynamics indicated that β-cells lose identifying markers such as insulin, proinsulin, IAPP, and protein tyrosine phosphatase receptor type N (PTPRN) prior to their destruction [111], potentially indicating a direct role for β-cells in inciting their own destruction by autoreactive T cells. Additionally, intra-and peri-islet T cell numbers were negatively correlated with disease duration and residual β-cell mass, with new-onset T1D donors possessing the highest degree of infiltration, regardless of the presence of β-cells (defined as islet cells expressing both Pancreatic And Duodenal Homeobox 1 (PDX1) and NKX6-1) [111].…”
Section: Multiplexed Analyses Of Human Pancreas Tissuementioning
confidence: 99%
See 2 more Smart Citations